AB0795 IMPACT OF PRIMARY HAND OSTEOARTHRITIS ON MICROSTRUCTURE AND BIOMECHANICS IN FINGER JOINTS. (June 2019) - Simon, David; Tascilar, Koray; Unbehend, Sarah; Bayat, Sara; Meinderink, Timo; Berlin, Andreas; Rech, Jürgen; Hueber, Axel; Schett, Georg; Kleyer, Arnd
Abstract : Background: Primary hand osteoarthritis (HOA) is a heterogeneous disease that is associated with erosive and osteoproliferative changes of the finger joints and progressive functional impairment. Despite these severe changes the effect of HOA on bone mass, microstructure and biomechanics in the affected skeletal regions is largely unknown. Objectives: To study the effect of HOA on bone microstructure, density and biomechanical properties using high-resolution peripheral quantitative computed tomography (HR-pQCT) of the finger joints and radius. Methods: HOA patients and healthy controls (HC) underwent HR-pQCT scans of the distal radius and 2 nd metacarpal (MCP 2) head. Total, trabecular and cortical volumetric bone mineral densities (vBMD) as well as microstructural and biomechanical properties (failure load) were determined. Failure load and scaled multivariate outcome matrices from distal radius and 2 nd metacarpal (MCP 2) head measurements were analyzed using multiple linear regression adjusting for age, sex and functional status and reported as adjusted z score differences for total and direct effects. Results: 105 subjects were included (76 HC/29 HOA). After adjustment, HOA was associated with significant changes in the multivariate outcome matrix of the MCP 2 head ( p < 0.001) explained by an increase in cortical vBMD (Δz = -1.07, p = 0.02) and reduction in the trabecular vBMD (Δz = 0.7, p = 0.09) Distal radius analysis did not show an overall effect of HOA however there was a gender-study group interaction explained by reduced trabecular vBMD in males (Δz = 1.23, p = 0.02). HOA was associated with lower failure load [-514 N (95%CI:-1025, -2), p=0.05]. Conclusion: HOA is associated with reduced trabecular and increased cortical bone mineral density and a reduction in radial bone strength. Impaired mobility might be an explanation for this reduction. These results underline the clinical importance of HOA-related functional impairment and indicate that HOA patients should be treated with awareness of increased fracture risk and antiosteoporotic treatment. Disclosure of interests: David Simon Grant/research support from: Novartis, Consultant for: Lilly, Speakers bureau: Janssen, Koray Tascilar: None declared, Sarah Unbehend: None declared, Sara Bayat: None declared, Timo Meinderink: None declared, andreas Berlin: None declared, Jürgen Rech Grant/research support from: Bristol-Myers Squibb and Celgene (greater than $10, 000), Consultant for: Bristol-Myers Squibb, Celgene, Chugai, GlaxoSmithKline, Janssen, Eli Lilly, Novartis, Roche, Sanofi aventis, and UCB (in total more than $10, 000), Speakers bureau: Bristol-Myers Squibb, Celgene, Chugai, GlaxoSmithKline, Janssen, Eli Lilly, Novartis, Roche, Sanofi aventis, and UCB (in total more than $10, 000), axel Hueber Grant/research support from: Novartis, Pfizer, Lilly, Consultant for: Lilly, GSK, Novartis, Janssen, Celgene, abbvie, Roche, Speakers bureau: Lilly, Janssen, Novartis, Celgene, Biogen, abbvie, BMS, Georg Schett: None declared, arnd Kleyer Grant/research support from: Lilly, Consultant for: Lilly, Speakers bureau: abbvie